The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Destination Management and Marketing 2020
DOI: 10.4018/978-1-7998-2469-5.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Dark Tourism

Abstract: This study looks at some primary points in the discourse of virtual dark tourism (VDT) formation. Derived from the spectrum of sound branding (SB), virtual reality (VR), coupled with augmented reality (AR), the case is used as a tool to support the claims of VDT. Findings suggest viewpoints for making death sites exclusive, and offer valuable clues to the design of VDT formation as an option to include death sites as market offerings of dark tourism. Guided by social constructionist research philosophy, couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…First, previous research operationalizes lighter and darker sides of dark tourism from characteristics of dark tourism sites (Handayani et al, 2017;Magee and Gilmore, 2015;Tang, 2014). Specifically, darker and lighter aspects are determined, depending on whether the dark tourism site is directly related to human death or not.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, previous research operationalizes lighter and darker sides of dark tourism from characteristics of dark tourism sites (Handayani et al, 2017;Magee and Gilmore, 2015;Tang, 2014). Specifically, darker and lighter aspects are determined, depending on whether the dark tourism site is directly related to human death or not.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Some sites are directly related to human death and disasters, while other sites are not. Depending on whether the dark tourism site is closely related to human death or not, the darker-lighter spectrum of dark tourism experiences arises (Handayani et al, 2017;Magee and Gilmore, 2015;Tang, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptingcontemporarytheoryofbrandingingeneralandofpersonificationand/orimpression management on death sites in particular, Handayani, Ivanov and Korstanje (2017) indicated that the design revolves around philosophical views of Smart Tourism coupled with Slow Tourism. Development of a death site is thus based on emotional and unique selling propositions (Kotler, Armstrong,Saunders&Wong,1999).Thisisinlinewithstudiesthatsuggestthattheaiminselecting SBformarketofferingsistodevelopsoundcreationsthatarederivedfromthedetailsofbrandvalues andthatcharacterizethebrand (Westermann,2008).Therefore,theselectionofsound,referringto music,shouldbeappliedinlinewiththephilosophiesofsmartandslowtourism.Smarttourism indicatestheapplicationofICTinsupportingthesupplyaspectsofattractionsanddestinationattributes (Gretzel,Sigala,Xiang&Koo,2015;Neuhofer,Buhalis&Ladkin,2015),encouragingtheco-creation ofsharedvalues,e.g.User-GeneratedContent(UGC) (Arriga&Levina,2008;Gretzel,Fesenmaier, Lee&Tussyadiah,2010;Jovicic,2017).SlowtourismadvocatestheuseofSBatthe"rightspeed", i.e.thetempoofslowandlocaltravel (Honoré,2009;Dickinson&Lumsdon;Caffyn,2009: Oh,Assaf&Baloglu,2014.Bythistoken,whileproliferationofICTcanbeinterpretedastheuse ofAR,theterm"rightspeed"canbeinterpretedasthe"righttempo"ofSBthatincharacterizing thetypeofdeathsiteanditssharedvalues.Technically,SBinvolvesselectingsongsthatdenote elementsofdarknessinthecircleoflife.AsHandayaniandGeorge(2017)putit,peoplelearnto (re)livethegoodnessofbeingalive,beingvulnerable,beinghappyandbeingsad.Thesemaybethe mostintriguingaspectsoflifewhichbecomecommodifiedandmayormaynotbeusefultohuman revelationandcontemplation.…”
Section: Sound Branding In Dark Tourism Spectrummentioning
confidence: 99%